The Russo-Ukraine War and Changing Global Power Dynamics (2014-23): A Neorealist Perspective - Rifat Ullah Rifat; Uzma Naz (ASIAN Journal of International Peace & Security (AJIPS), 2024)
The Russo-Ukraine War in 2022, despite historical evidence of enduring tensions between the two nations, came as a surprise for the world, challenging the U.S.-led global political order. Understanding the drivers of conflict and shifting balance of power, especially in Eurasia, is critical for academic discourse in international relations and assessing future geopolitical trends. The paper investigates the Russo-Ukraine War using a neorealist lens as a theoretical framework, adopting qualitative research methodology with a thematic analysis technique. For focused research, besides investigating the broader historical linkages of the conflict, the time horizon is delimited from 2014-23. The research questions focus on the genesis of the conflict by exploring key drivers, intersecting interests of the global powers and how the War is impacting the geopolitical landscape of Eurasia in particular and global political order in general. The study addresses the research gaps in exploring different scenarios as the end state of the conflict and their implications for the global powers and world order. Findings from detailed discussion reveal that the Russo-Ukraine War is not just a territorial dispute between the two nations but has broader geostrategic implications for the region and beyond. The conflict has the potential to reshape the alliances and exacerbate the global powers’ competition, redefining the context and complexion of the emerging world order.